(untitled) (Revista de Artes Marciales Asiáticas, 2023)
The aim of this study was to investigate the relationship between judo specific test performances and physical fitness of prepubescent judo athletes. Forty male judo athletes aged 10-13 voluntarily participated. Athletes completed special judo fitness test (SJFT), hikisdashi uchi-komi test (HUT), judogi grip strength tests, and performance-related physical fitness components tests (aerobic power, strength, agility, explosive power, body composition). Correlation coefficients were used to analyze the relationship between the judo specific tests and physical fitness performances. Significant correlations were found between total throw numbers during SJFT, HUT performance, isometric and dynamic judogi grip strength test performance and general performance-related physical fitness tests. Also, negative correlations were found between judo specific tests performances and body fat percent. It can be concluded from the study that total throws in SJFT, 20 s HUT and dynamic judogi grip strength tests can be used to monitor performances of prepubescent judo athletes as these tests present large significant correlations with performance related physical fitness tests.